Peningkatan Sikap dan Praktik tentang Pertolongan Pertama pada Kecelakaan Lalu Lintas pada First Person on Scene - Risa Herlianita; Awwalul Hijriyah; Nadhiratul Layli Insyira Kautsariyyah; Anis Ika Nur Rohmah (Lembaga Pengembangan Kinerja Dosen, 2023)
First person on Scene or lay people around the scene can help provide first aid to accident victims. However, the general public around the accident did not provide assistance to accident victims. From these problems, a solution is needed by providing appropriate information regarding first aid in first person on scene accidents, so that the severity of injury can be prevented and further reduce the mortality rate caused by traffic accident. We designed community service-based study to increase first person on scene in Malang through increasing the knowledge of the first person on scene about managing the first aid in road traffic accident. The method applied in this activity is training with pre-test and the first post-test about first aid. The data were analyzed by descriptive analysis, and a paired t-test was performed to test the pre-test and post-test data. The total participants who participated in this activity were 40 people. The results showed that there was an increase in attitude and practice about first aid in traffic accident. The training, discussion, and distribution of pocketbooks can increase the attitude and practice about first aid in traffic accident of the first person on scene in Polowijen Village.